SYSTEM-POLITICAL CHARACTERISTICS OF LEGAL CULTURE - Absattarov Galymzhan Raushanbekovich (Scientific Journal of Pedagogy and Economics, 2020)
The article based on the materials of Kazakhstan examines the system and political characteristics of legal culture that have not been studied in political science yet. The paper also regards in more detail the politological aspects of the essence, concept, and definition of Kazakhstani legal culture. Based on the studies, it was concluded that the legal culture of Kazakhstan as a complex systemic formation is a combination of material and spiritual achievements in the legal, political life of Kazakhstani society. Thus, the level of legal culture of Kazakhstan reflects the degree of maturity of the Kazakh citizen's civilization, his way of thinking and behavior standards. At the same time, it acts as a meaning-bearing and meaning-determining aspect of Kazakhstani human practice and its results in the legal, political life of society. Legal culture is a political phenomenon, a certain nature and level of activity of an individual, during which he/she gains or develops his/her legal, moral and political knowledge, skills. At the same time, the article focuses on issue discussion.